The Effect of Interval Training on the Improvement of Vo2max in Karate Athletes in INKADO Province of Bali - Kadek Yogi Parta Lesmana; Syarif Hidayat; Anak Agung Ngurah Putra Laksana; Luh Ita Mahendrayani (Mimbar Ilmu, 2025)
The physical fitness of the Bali province's Inkado karate athletes is still not good, as can be seen from the ineffective movements they make when playing due to fatigue. This study aims to determine the effect of interval training on the physical fitness of Inkado karate athletes in Bali Province. This training can improve their physical fitness, thus maintaining their fitness levels during performance. This study was a pre-test and post-test group study, a single-group experiment with no comparison group. The sampling technique used total sampling, with 35 athletes participating. The instrument used in this study was the Multistage Fitness Test. From the results and discussion, it can be concluded that there was a significant improvement after the interval training treatment. A limitation of this study is the inability to control for external conditions such as rest and nutrition intake. Therefore, further monitoring is needed to maximize athlete performance.